Mcdonald's Malaysia@Gerbang Alaf Restaurants Sdn Bhd / Mohd Hafiz Ahmad ... [et al.] - Ahmad, Mohd Hafiz; Eshkak, Eszrul Anuar; Sanusi, Yus Norfatinsafiah; Murshid, Fazila Fadil (2018)
The first section of this case study will introduce the background of Fast Food Industry. After the brief introduction is problem statement for the industry and purpose of study. The next section is Information about the Fast Food Company was select - McDonald's Malaysia. The information is about background of the company, organizational structure, product/services, business strategy and financial achievement. Next is the analysis of the company. The analysis is being analyzed based on the SWOT Analysis and Business Model Canvas. This analysis is to analyzed McDonald's strengths and also its weaknesses the next segment will be the finding and discussions. After that the conclusions will be reported. Lastly, the issues and problems are brought up and recommendations are given to improve the situation.